Can dalbavancin be used as a catheter lock solution?. Issue 7 (July 2018) - Díaz‐Ruíz, Cristina; Alonso, Beatriz; Cercenado, Emilia; Cruces, Raquel; Bouza, Emilio; Muñoz, Patricia; Guembe, María
Abstract : Purpose. : The new lipoglycopeptide dalbavancin has only been approved for acute bacterial skin and skin structure infections. However, its alternative use as a catheter lock solution could facilitate the conservative management of catheter‐related bloodstream infection. Our objective was to assess the stability and activity of dalbavancin alone and in combination with heparin against methicillin‐resistant Staphylococcus aureus (MRSA) and methicillin‐resistant Staphylococcus epidermidis (MRSE) biofilms. We also compared the results with those obtained with vancomycin alone and in combination with heparin. Methodology. : We used a 96‐well plate in vitro model based on 24 h biofilms of MRSA and MRSE (ATCC 43300, ATCC 35984 and one clinical strain of each). The biofilms were exposed to dalbavancin (0.128 mg ml −1 ) and vancomycin (5 mg ml −1 ) alone and in combination with heparin (60 IU). The median percentage reductions in metabolic activity, biomass, bacterial load, and cell viability for each solution were compared. Results. : Dalbavancin combined with heparin significantly reduced the median [interquartile range (IQR)] percentage of metabolic activity in MRSA biofilms compared with vancomycin [90.0 % (70.4–92.9 %) versus 35.0 % (14.8–59.6 %), P =0.006]. For the remaining variables studied, the combination was not inferior to vancomycin for MRSA and MRSE. Conclusions. : Dalbavancin proved to be active against MRSA and MRSE biofilms. The combination of dalbavancin with heparin is a promising catheter lock solution that has the advantage of locking the catheter at home for 7 days.